2015
DOI: 10.1161/circoutcomes.114.001398
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Dabigatran Use, Safety, And Effectiveness In a Population-Based Cohort of Patients With Atrial Fibrillation

Abstract: Background-Sex differences were observed with regard to warfarin treatment in patients with atrial fibrillation, with women having a higher risk of stroke compared with men. We aimed to compare sex differences in use, safety, and effectiveness of dabigatran. Methods and Results-We conducted a population-based cohort study of patients with atrial fibrillation using administrative data in Quebec, Canada, 1999 to 2013. Men and women who filled a prescription for dabigatran (110 and 150 mg bid) were compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…This study of ≈35 000 nonvalvular AF patients from a complete population shows that treatment with DOACs is associated with reduced risk for a combined end point of all‐cause stroke or death compared with warfarin, even after adjustment for baseline differences. Consistent with the pivotal clinical trials comparing warfarin and DOACs, meta‐analysis of clinical trials data, and other population‐based analyses, the protective effect of DOACs in our study is driven by lower rates of hemorrhagic stroke and death. DOAC treatment is not associated with increased risk of myocardial infarction.…”
Section: Discussionsupporting
confidence: 88%
“…This study of ≈35 000 nonvalvular AF patients from a complete population shows that treatment with DOACs is associated with reduced risk for a combined end point of all‐cause stroke or death compared with warfarin, even after adjustment for baseline differences. Consistent with the pivotal clinical trials comparing warfarin and DOACs, meta‐analysis of clinical trials data, and other population‐based analyses, the protective effect of DOACs in our study is driven by lower rates of hemorrhagic stroke and death. DOAC treatment is not associated with increased risk of myocardial infarction.…”
Section: Discussionsupporting
confidence: 88%
“…For example, women may be more likely to decline OAC therapy, particularly warfarin, due to concerns for bleeding, inconvenience, or lack of social support (ie, transportation for international normalized ratio check) . Additionally, providers may perceive increased frailty or bleeding risk in women compared to men because women have been shown to have higher rates of bleeding while on warfarin and after cardiac interventions . Our finding of greater increases in NOAC use in women compared to men may support the notion that higher bleeding risk contributed to past sex differences in OAC use when therapy options were more limited.…”
Section: Discussionsupporting
confidence: 56%
“…Second, the development of non–vitamin K oral anticoagulants (NOAC) has expanded treatment options for patients with AF. NOACs have a lower risk of major bleeding and equivalent stroke rates compared to warfarin . Therefore, it is possible that sex differences in OAC use have diminished with the introduction of NOACs.…”
Section: Introductionmentioning
confidence: 99%
“…However, sex specific outcomes were not reported in these observational studies. A Canadian study 41 , using a propensity matched analysis involving 31,786 women and 31,324 men with AF from administrative data, compared sex specific effectiveness of DABI (110 mg and 150 mg) to Warfarin. The study concluded that DABI use was associated with similar stroke risk compared to Warfarin in both sexes, but was protective against major bleeding only in men.…”
Section: Discussionmentioning
confidence: 99%